Health and safety issues among construction workers in Bangladesh - Mamin, Firoz Ahmed; Dey, Ganesh; Das, Shazal Kumar (International Journal of Occupational Safety and Health, 2019)
Background: Bangladesh is a rapidly developing country. Lots of infrastructures are set up every year. A large number of people are working in the construction industry. Work related injuries and deaths of construction workers are common. The aim of this study was to find the health and safety awareness of informal construction workers. Methodology: This study was a cross sectional study by using a preset questionnaire among the construction workers in Bangladesh. Results: Participants of this study had lower income and education. About 87% of participants did not receive any health and safety training and did not wear safety equipment when they were working. About 57% of the participants had a history of injury. This study also found that the main reasons for the non-use of safety equipment were lack of safety equipment, motivation and training. Conclusion: Construction workers are not adequately aware about health and safety issues that relate to them.